Praktik Pemberian Makanan dan Praktik Kesehatan dengan Kejadian Balita dengan Gizi Kurang - Siti Gabena Sir; Evawany Y. Aritonang; Jumirah Jumirah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between feeding practices and health practices for under-five children with malnutrition in Sekip Village, Lubuk Pakam District, Deli Serdang Regency. This study used a cross-sectional approach with a sample size of 100 respondents. Sampling was done using cluster technique and simple random technique (roll of paper). The resulting data were analyzed univariate and bivariate using the chi-square test (α = 0.05). The results showed that under-fives who experienced malnutrition were 34%. Simultaneously, mothers' feeding practices and health practices to children under-five were partly categorized as bad, namely 56 people (56%) and 54 people (54%). In conclusion, there is a relationship between feeding practices and health practices on undernutrition in children under-five. Keywords: Toddler, Malnutrition, Health Practices, Feeding Practices